(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
this article talks about the conversion of spiritual and cultural wealth of people into consumption, the importance of human needs in this regard. It was also emphasized that spiritual activity, which is one of the factors that further improves the spiritual and cultural life of the society and determines its progress, must always be maintained in proportion to spiritual needs.